Fueling innovation management research: Future directions and five forward-looking paths - Jelena Spanjol; Charles H. Noble; Markus Baer; Marcel L. A. M. Bogers; Jonathan Bohlmann; Ricarda B. Bouncken; Ludwig Bstieler; Luigi M. De Luca; Rosanna Garcia; Gerda Gemser; Dhruv Grewal; Martin Hoegl; et al. (Journal of Product Innovation Management, 2024)
Research about innovation management explores how the future is created—who is creating it (organizations, collaborations, etc.), for what aims (customer satisfaction, market performance, etc.), and with what broader effects (social, environmental, etc.). With this extended essay, we explore the potential futures of innovation management research in three ways. First, we briefly review the history of past research agendas and priorities published in the Journal of Product Innovation Management (JPIM), highlighting three broad topic areas (technological, social/environmental, and organizational) that have emerged over time and their potential disruptive implications for innovation management research. Second, we describe the outcome of a gathering of leading scholars in innovation management tasked with the challenge of identifying critical research paths for our field. This collaboration resulted in five "deep dive" essays into areas ripe for innovation management research in the years ahead: liquid innovation, artificial intelligence in innovation, business model innovation, public value innovation, and responsible innovation. Third, we reflect on this expansive effort and offer a discussion of implications (tensions, challenges, and opportunities) for future innovation management scholarship.
Keywords: 650; artificial intelligence in innovation; business model innovation; future of innovation management; liquid innovation; public value innovation; research agenda; research directions; research priorities; responsible innovation